Occurrence of collar rot on berseem (Trifolium alexandrinum L.) caused by Sclerotium rolfsii and its molecular characterization in India. (10th January 2022) - Mahesha, H. S.; Keerthi, M. C.; Manjunatha, N.; Vinaykumar, H. D.; Singh, Tejveer; Bhargavi, H. A.; Saini, Ravi Prakash; Ahmed, S.; Yadav, V. K.
Abstract: Berseem ( Trifolium alexandrinum L.) is one of the important legume fodder crops. It is widely grown in Central and Northern parts of India during winter season. Disease symptoms resembling to collar rot was observed in the breeder seed production and research fields of berseem at ICAR-IGFRI, Jhansi, Uttar Pradesh, India in March 2019 and April 2020. Disease incidence was ranged from 15–20% and 20-25% in 2019 and 2020, respectively. Disease symptom appeared as water soaked lesions on surface of collar region followed by the development of rotten areas with white mycelial mass and finally plants were dried. The associated pathogen was isolated and identified as Sclerotium rolfsii (Teleomorph: Athelia rolfsii ) on the basis of morphological characters and sequence analysis of ITS, LSU and SSU regions of rDNA. Artificial inoculation of pathogen revealed cent per cent disease incidence and wilting of plants. To best of our knowledge, this is first complete report on etiology of collar rot disease caused by Sclerotium rolfsii on berseem in India.